(3GdbQUfI hCef GdHMQ GdCMeQ (B/s - (3GdMeOGfj, eUWai CMeO aDGO aJGMs ((3YeGf, GdCQOf (B:s (3OGQ CeLO ddfTQ h GdJhRjY ;s (3EHUGQ fGTQhf hehRYhf,s, 2020)
(3dbO CUHM GdMaGX Ydi GdCef GdHMQj CMO GdVQhQGJ GdCSGSjI ddeLJeY GdOhdj GdPj jYJeO HOQLI cHjQI Ydi GdHMGQ aj YedjI Gdfbd, hPdc dQNU JcGdjag hMLe hcejI GdHVGFY GdJj jecf Cf JMedgG GdHhGNQ hSaf Gdfbd, dPdc aEf JhajQ Hjf GdMeGjI GdHMQjI dgPg GdSaf jSGYO aj EROgGQ hOYe GdJLGQI GdOhdjI Hjf Ohd GdYGde, dG SjeG hCf gfGc JQGHWG cHjQG eaghe GdbQUfI GdHMQjI heOi JCKjQgG HGdHMGQ hGdJj JSge eY YhGed CNQi aj EfYOGe GdCef GdHMQj, GdCeQ GdPj jDOj HGdOhd Cf JSJTYQ NWQ GdJgOjOGJ GdJj jJYQU dgG CefGdHMGQ, aJdLC Edi YedjI JOhjd GdCef hHGdJGdj jUHM gfGc MGLI eGSI dLghO LeGYjI JSYi Edi JMbjb GdCef GdOhdj, hdCf GdJgOjOGJ GdJj JhGLg GdeeQGJ GdeGFjI GdHMQjI hNWhW ehGUdGJgG JQej HJOGYjGJgG GdeHGTQI Ydi EeOGOGJ GdCef GdZPGFj hCef GdWGbI hGdCef GdHjFj hGdJj JJeKd fhYG ef ddCef GdOhdj, agfGc GdYTQGJ ef GdgLeGJ JWGd GdSaf GdJLGQjI HhGSWI GdEYJOGA Ydi GdSdGeI GdHTQjI hJTcd JgOjOG CYeGd GdbQUfI GdHMQjI(B. (3dPdc aEf GdhVY GdMQL GdPj HGJ jTgOg GdHMQ GdCMeQ, aQV eLehYI ESJQGJjLjGJ CefjI JMed aj KfGjGgG VQhQI GdJfSjb Ydi GdeSJhi GdOhdj dhVY GdNWW GdCefjI GdYGdejI ddbVGA Ydi GdeNGWQ GdJj JgOO gPGa GdeeQ, hdEf GdHMQ GdCMeQ hGdCbGdje GdeJeGSI eYg cGdbQf GdEaQjbj ef GdLgI GdEaQjbjI hGdNdjL GdYQHj ef GdLgI GdBSjhjI, aVdkG Yf GdeMjW GdgfOj, chf eKdKG ESJQGJjLjG egeG MXi HEgJeGe Gdbhi GdYGdejI GdeJfGaSI Ydi JbSje GdYGde Edi efGWb fahP, aEf gOa JCejf eUGdMgG GdMjhjI aj gPg GdefGWb UGZ eOQcgG dCefGdHMQ GdCMeQ(B.s
(3HHdjhLQGajI (B: (3UaMI (B297-351.s
Keywords: (3GdCef GdOhdjs -- (3GdHMQ GdCMeQs; (3GdbQUfIs -- (3GdHMQ GdCMeQs; (3GdbQUfI (B((3bGfhf Ohdj(B)s -- (3GdHMQ GdCMeQs